Hydroacoustic, Meteorologic and Seismic Observations of the 2016 Nansen Ice Shelf Calving Event and Iceberg Formation - Dziak, R. P.; Lee, W. S.; Haxel, J. H.; Matsumoto, H.; Tepp, G.; Lau, T.-K.; Roche, L.; Yun, S.; Lee, C.-K.; Lee, J.; Yoon, S.-T. (Frontiers in Earth Science, 2019)
On 7 April 2016, the Nansen Ice Shelf (NIS) front calved into two icebergs, the first large-scale calving event in >30 years. Three hydrophone moorings were deployed seaward of the NIS in December 2015 and over the following months recorded hundreds of short duration, broadband (10-400 Hz) cryogenic signals, likely caused by fracturing of the ice shelf. The majority of these icequakes occurred between January and early March 2016, several weeks prior to the calving observed by satellite on 7 April. Barometric pressure and wind speed records show the day the icebergs drifted from the NIS coincided with the largest low-pressure storm system recorded in the previous 7 months. A nearby seismic station also shows an increase in low-frequency energy, harmonic tremor, and microseisms on 7 April. Our interpretation is the northern segment of the NIS leading edge broke free during mid-January to February, producing high acoustic energy, but the icebergs remained stationary until a strong low-pressure system with high winds freed the icebergs. As the unpinning of Antarctic ice shelves is not a well-documented process, our observations show that storm systems may play an under-appreciated role in Antarctic ice shelf break-up.